Correlation of stock market returns in the West African region from 2008 to 2016 - Eseosa Obadiaru; Alex Omankhanlen; Barnabas Obasaju; Henry Inegbedion (Investment Management & Financial Innovations, 2019)
Stock markets over the world have become more interconnected due to activities of foreign investors in search for alternative financial assets and markets to invest in order to diversify their portfolio. Stock market indices and index returns have been known to reflect linkages between different markets. This study assesses the extent of correlation of stock market index returns in West Africa and those of the United States of America (US) and United Kingdom (UK) from 2008 to 2016. The correlation between the index returns for the entire sample period and yearly samples were considered for Nigeria, Ghana, the BRVM, the USA and the UK. The indices selected for the five countries considered are the Nigerian All-Share Index, Ghanaian Composite Index, the BRVM Composite Index, the Financial Times 100 Index and the Standards and Poor’s 500 Index. Daily index returns data were used for the study and analyzed using correlation and multiple regression analysis. Findings revealed that the returns of the pairs of the United States of America (US) and the United Kingdom (UK) exhibited stronger positive correlation with each other than the other market pairs in the study both in the entire sample period and the yearly sub-period analysis. The correlations between the other market pairs were either positively or negatively weak or very weak indicating more diversification opportunities.